World Economic Outlook, April 2021 : Managing Divergent Recoveries. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2021)
The global economy is climbing out from the depths to which it had plummeted during the Great Lockdown in April. But with the COVID-19 pandemic continuing to spread, many countries have slowed reopening and some are reinstating partial lockdowns to protect susceptible populations. While recovery in China has been faster than expected, the global economy's long ascent back to pre-pandemic levels of activity remains prone to setbacks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; International Agreements and Observance; International Organizations